Motorized Hose Rolling Tool for Firefighter: Design and Fabrication Process - Mahmood, Salwa; Mustapha, Mohammad Luqman Hakim; El Bakri, Helmy Mustafa; Abdul Rahman, Ismail; Badulrudin, Mohd Fahmi (UUM Press, 2024)
This paper addresses the critical problem of low back pain (LBP) among firefighters, particularly during hose rolling operations. The main objective is to lower the average probability of LBP risks by introducing a motorized hose roller for such activities. The development of this tool is guided by prior studies which included a survey. The design and fabrication processes of the motorized hose roller involved assessing existing patents for novelty, employing Solid Work software for design, using a morphological chart for concept selection, and finalizing fabrication through metal casting and wiring. Based on the experiment that had been conducted, the conventional hose rolling methods recorded an average LBP risk probabilities of 58.22%, while the motorized hose rolling tool method significantly reduced these risks to 17.44%, representing a 40.78% reduction of LBP risks. These findings highlight the effectiveness of motorized hose rolling tool and its potential as a safer alternative to existing methods, offering vital insights for improving occupational health and safety in hose rolling operation. This research further explores the design and fabrication of motorized tools, emphasizing their potential to alleviate the physical loads encountered by firefighters